Effects of internal concentration polarization and membrane roughness on phenol removal in extractive membrane bioreactor - Liao, Yuan (2019)
Recent studies have proved the advantages of novel composite membranes in the extractive membrane bioreactor (EMBR) for recalcitrant organic wastewater treatment. However, more systematic research into membrane properties and mass transfer effects are required. This study investigates the role of internal concentration polarization (ICP), including concentrated and diluted ICP, in an aqueous-aqueous extractive process, and the coupled effects of membrane roughness and hydrodynamic conditions on membrane performance in both cross-flow EMBR (CF-EMBR) and submerged EMBR (S-EMBR) processes. To study these factors, a nanofibrous composite membrane with a four-tiered structure, consisting of a dense polydimethylsiloxane (PDMS) selective layer, a polyvinylidene fluoride (PVDF) nanofibrous sublayer, a non-woven mechanical support and a rough micro/nano-beaded layer, has been developed for the EMBR by electrospinning and spray-coating. A diluted ICP, which occurred when the selective layer faces receiving water (SL-Rw), was less severe than a concentrated ICP in the selective layer facing feed (SL-F) orientation. It resulted in higher overall membrane mass transfer coefficients (k0's) in the SL-Rw mode during the aqueous-aqueous extractive tests. In addition, less biofilm was observed on the smooth PDMS surface after 14-days CF-EMBR and S-EMBR operations in the selective layer facing biomedium (SL-Rbio) mode. In contrast, in the SL-F mode during EMBR operations, the ridges and valleys on the membrane surface were able to provide a more favourable micro-environment for microorganisms and protect them from external stresses. The mature micro-colonies that developed in the SL-F mode clogged the membrane support and enhanced concentrated ICP, resulting in a significant reduction of k0's by more than 58%. Moreover, as the shear force on the membrane surface due to up-flow of air bubbles in the S-EMBR could mitigate the biofilm attachment, the most effective biofilm control strategy found in this study was to operate the nanofibrous composite membrane in the S-EMBR configuration with a smooth selective layer facing the biomedium. This effectively decreased the amounts of protein by 86%, polysaccharides by 88% and total suspended solids (TSS) by 89% in the biofilms on membrane surface, and achieved the highest stable k0 of 7.0 × 10−7 m/s.